Lytic bacteriophages targeting multidrug-resistant Pseudomonas aeruginosa in Moschus berezovskii: isolation, characterization, and therapeutic efficacy against bacteremia - Qingxia Hu; Yanjie Zhang; Ni Lv; Yahao Kang; Saba Nasir; Ruiqing Wang; Jiahao Qu; Jiadeng Jiang; Xiao Li; Xinglong Wang (Virology Journal)
Abstract Pseudomonas aeruginosa (P. aeruginosa) is an important zoonotic pathogen. It is also the primary causative agent of systemic infections in the endangered Moschus berezovskii. The emergence of multidrug-resistant strains of P. aeruginosa has made these infections increasingly difficult to control, and bacteriophages are considered important alternatives or adjuncts to antibiotic therapy. This study isolated P. aeruginosa strains that induce suppurative infections in Moschus berezovskii from a farm in Shaanxi Province, China. The bacteriophages vB_PaeP_FMD5 (FMD5) and vB_PaeM_H24-1 (H24-1) were isolated using these bacteria as hosts. The safety and practicality of the two phages were analyzed through methods such as biological characteristic assessment, whole genome sequencing analysis, and animal experiments. FMD5 is classified within the Podoviridae family, whereas H24-1 belongs to Myxoviridae. Biological characterization revealed that both FMD5 and H24-1 exhibit tolerance to temperature, pH, chloroform, and Ultraviolet(UV) exposure. The optimal multiplicity of infection (OMOI) for FMD5 and H24-1 were 0.01 and 0.1, respectively, and the burst sizes from the one-step growth curve were 200 PFU/cell and 150 PFU/cell, respectively. In vitro inhibitory assays demonstrated that FMD5, H24-1, and their cocktail exerted a favorable inhibitory effect for up to 11 hours. Whole genome sequencing confirmed that both phages possess double-stranded DNA genomes, with FMD5 having a length of 72,254 bp and a G+C content of 55.16%, containing 91 ORFs(Open Reading Frame)​, whereas H24-1 has a genome length of 66,281 bp, a G+C content of 56.26%, and encompasses 94 ORFs. No drug-resistance genes, virulence factors, or lysogenic genes were identified in either phage. Phylogenetic analysis of conserved genes revealed that FMD5 is closely related to the previously published Pseudomonas phage LP14 (LP14), while H24-1 is closely related to the previously published Pseudomonas phage vB_PaeM_LS1(LS1), but both are newly discovered bacteriophages. In a mouse model of bacteremia treated with bacteriophages, both individual phages and the cocktail exhibited favorable therapeutic effects. The two novel bacteriophages isolated in this study exhibit efficient and stable characteristics. They demonstrate sound therapeutic effects against bacteremia in mice caused by multidrug-resistant P. aeruginosa, suggesting their great potential as alternatives or adjuncts to antibiotic therapy for treating infection.